2011
DOI: 10.1111/j.1945-5100.2011.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel tracks made by impacts of glycine: Implications for formation of bulbous tracks in aerogel and the Stardust mission

Abstract: Abstract-Impacts of small particles of soda-lime glass and glycine onto low density aerogel are reported. The aerogel had a quality similar to the flight aerogels carried by the NASA Stardust mission that collected cometary dust during a flyby of comet 81P ⁄ Wild 2 in 2004. The types of track formed in the aerogel by the impacts of the soda-lime glass and glycine are shown to be different, both qualitatively and quantitatively. For example, the soda-lime glass tracks have a carrot-like appearance and are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…(2009b) showed that polystyrene beads leave well‐defined Type A tracks when impacted on low density aerogel at 1.2 km s −1 . However, subsequent reexamination of tracks from similar polystyrene beads impacted at approximately 6 km s −1 (Nixon et al. 2012) shows that these particles undergo substantial mass loss, and has revealed a rather different, much broader, track shape, like that which we have here designated as Type A*.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…(2009b) showed that polystyrene beads leave well‐defined Type A tracks when impacted on low density aerogel at 1.2 km s −1 . However, subsequent reexamination of tracks from similar polystyrene beads impacted at approximately 6 km s −1 (Nixon et al. 2012) shows that these particles undergo substantial mass loss, and has revealed a rather different, much broader, track shape, like that which we have here designated as Type A*.…”
Section: Discussionmentioning
confidence: 82%
“…2011), although the depth of penetration may also partly depend upon the degree of ablation and abrasion suffered (for example, compare the alumina impacts of Hörz et al. [2009] with the glycine of Nixon et al. [2012]), and depth may therefore not be related to the particle density alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was difficult to clearly establish an extra-terrestrial origin for the glycine based on analysis of the aerogel alone -instead analysis of the surfaces of nearby aluminum foils was required (Elsila et al, 2009). Laboratory impact experiments firing glycine grains into aerogel (Nixon et al, 2012) showed that in impacts at 6 km s À1 the captured grains had lost the majority of their pre-impact mass in the capture process, but no tests were carried out on the aerogel to determine where the missing material had gone or how it may have been processed in the impact event. Similarly, impacts on aerogel by polystyrene microparticles show that 84% of the mass is lost during capture at speeds of 6 km s À1 (Burchell et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%